Emergency Animal Boarding: A Social Return on Investment - Gemma C. Ma; Jioji Ravulo; Ursula McGeown (Animals, 2023)
Companion animals play a central role in many families and are especially valued by those who are socially isolated. Crisis situations such as acute hospitalizations, homelessness, and natural disasters can make it difficult to preserve the human–animal bond and can result in animals being surrendered or euthanized. Social support programs like the RSPCA NSW Emergency Boarding and Homelessness program support people experiencing crisis situations with emergency pet boarding, access to veterinary treatment and individualized case management. This study aimed to estimate the social return on investment (SROI) for this program using the standard SROI methodology. In-depth interviews were conducted with 13 program stakeholders and questionnaire responses were received from 29 program clients. Outcomes were quantified for four stakeholder groups: program clients, client’s animals, RSPCA Inspectors, animal pounds, and shelters. Clients and their animals experienced the bulk of the benefit from the program, estimated to have a combined value of over AUD 5 million for the 2020–2021 financial year. The estimated social return on investment was AUD 8.21 for each AUD 1 invested. The study demonstrates that keeping people together with their companion animals or ensuring they are reunited as soon as possible can reduce stressors and improve outcomes for people and animals.